Physical and mechanical properties of heat‐damaged structural concrete containing expanded polystyrene syntherized particles. (17th January 2014) - Lo Monte, Francesco; Bamonte, Patrick; Gambarova, Pietro G.
Summary Materials recycling for sustainable concrete constructions are favoring the replacement of ordinary aggregate with waste materials, in the form of either solid particles or small void‐formers. This is the case of expanded polystyrene syntherized (EPS) concrete containing EPS particles—or beads—whose high‐temperature residual behavior is investigated in this project. Two EPS mixes and one reference mix (fc = 25–30 MPa) are tested in compression and tension after a thermal cycle at the reference temperature of 20°C, 150°C, 300°C, 500°C, and 700°C. The thermal diffusivity and the mass loss up to 700°C are investigated as well. The normalized mechanical decay of the two EPS concretes turns out to be slightly higher than that of ordinary concrete, but on the whole, the behaviors are rather close, while the thermal diffusivity of EPS concrete is definitely lower, to the advantage of its insulating capability. Damage indexes are also worked out on the basis of the elastic modulus and of the ultrasonic velocity, in order to have information on the possible void‐induced nonlinear effects. The still open problem, however, is whether the game (polystyrene recycling and mass reduction) is worth the candle (more cement and additives). Copyright © 2014 John Wiley & Sons, Ltd.